Validation of revised trauma score (RTS) in the emergency room (ER) of Kasr Alainy, (Cairo University hospital) - Amgad Elnaseh Asaad; Doaa Ahmed Mansour; Hisham Ahmed Aboueisha (Cairo : Amgad Elnaseh Asaad, 2014)
RTS serves in prioritizing trauma care management and in predicting trauma mortality and disability. To validation of the RTS as a tool to predict injury severity and hence disability, mortality and need for ICU, we collected the data of 200 consecutive patients presented in Kasr Alainy with blunt trauma. Their RTS was calculated and they were followed up. Data was collected and analyzed. Of the 200 patients, 143 patients had an RTS of 12, 27 an RTS of 11, 13 an RTS of 10, 10 an RTS of 9, 4 an RTS of 8,1 an RTS of 7 and 2 an RTS of 5. There was a proportionate increase in ICU need and mortality with decreasing RTS system
Thesis (M.Sc.) - Cairo University - Faculty of Medicine - Department of General Surgery
Issued also as CD
Keywords: Blunt Trauma; Trauma score; Triage system Revised trauma score